Incidence and Radiographic Predictors of Valgus Tibiotalar Tilt After Hindfoot Fusion. (May 2017) - Miniaci-Coxhead, Sara Lyn; Weisenthal, Benjamin; Ketz, John P.; Flemister, A. Samuel
Background: The development of valgus tibiotalar tilt following hindfoot arthrodesis is rarely discussed in the literature. The purpose of this study was to determine the incidence of valgus tibiotalar tilt and to evaluate if there were any radiographic predictors for the development of valgus tibiotalar tilt. Methods: Patients who underwent hindfoot fusion between January 1, 2004 and December 31, 2013 were identified. Charts were reviewed for demographic information and operative details. Preoperative and postoperative radiographs were reviewed for the development of tibiotalar tilt, and standardized measurements and angles were calculated. A total of 187 patients were included. There were 106 (56.7%) females and 81 (43.3%) males. The average age was 52 years (range, 11-82 years). The most common indication for surgery was adult-acquired flatfoot deformity (n = 92, 49.2%), followed by arthritis (n = 83, 44.4%). The most common procedure was triple arthrodesis (n = 101, 54%). Twenty-seven patients demonstrated tibiotalar tilt preoperatively. Results: A total of 51 patients (27.3%) developed valgus tibiotalar tilt postoperatively at an average of 3.6 months after surgery. We found that an increase in the preoperative Meary (lateral talar–first metatarsal) angle (hazard ratio, 1.039; 95% confidence interval, 1.002-1.077; P < .05) was associated with the development of tibiotalar tilt. An increase in the postoperative Meary angle (hazard ratio, 1.052; 95% confidence interval, 0.999-1.108; P = .0528) approached significance for the development of tibiotalar tilt. Conclusion: The development of valgus tibiotalar tilt following hindfoot fusion was a notable phenomenon, occurring in 27% of our patient population. The preoperative Meary angle was the only radiographic measurement that was significantly associated with the development of valgus tibiotalar tilt, although the postoperative Meary angle approached significance. These findings should encourage surgeons to be aware of patients with large deformities and of their propensity to develop a valgus deformity about the ankle. Level of Evidence: Level III, retrospective comparative series.